Morphological changes in the respiratory system: an MRI investigation of differences between the supine and left lateral decubitus positions. Issue 6 (2nd November 2021) - Little, J. Paige; Chapman, Erin; Parr, Adam; Moloney, Gregory; Bowler, Simon; Labrom, Robert D.; Askin, Geoffrey N.
ABSTRACT: Preoperative serial imaging of the torso is typically carried out in the supine position (e.g. magnetic resonance imaging [MRI], CT), however, intraoperative patient positioning is often lateral, and for some procedures may involve deflation and/or ventilation of the lungs. This study examined the differences in lung anatomy between the supine and lateral decubitus positions. MRI data for 10 healthy female adult volunteers lying in supine and left lateral decubitus positions were analysed. 2D measurements in coronal, transverse and sagittal planes were used to calculate the cross-sectional area, height and width of the lungs and the shape of the diaphragm. 3D surface reconstructions of the lungs and bronchi were created to determine the volume change between positions. The volume of the right lung was found to increase due to the caudal shift of the insertion points of the right hemidiaphragm (mean volume increase of 25% ± 11, p ≪ 0.05). There was minimal change in the left lung parameters with no significant change in left lung volume between positions (mean volume change = 0% ± 44%, p > 0.05). This study presents new information characterising anatomical changes in the respiratory system when a patient is positioned in the lateral decubitus compared to supine position.